THE ROLE OF THE STATE IN FORMING THE INNOVATIVE ECONOMICS: THE CASE OF GEORGIA (Globalization and Business, 2023)
The modern paradigm of economic development shows that an important factor affecting economic development is not only natural resources but also innovative approaches that stimulate the competitiveness of the country. Forming innovative economics in the direction of education, trade, investment, and financial decentralization requires the selection of effective tools for innovative economics formation, which creates a fertile foundation for the introduction of innovations in these areas. And this is achieved by optimal coordination of different combinations of state regulation instruments.       Relevance of the topic: Determining the importance of the role of the state in forming innovative economics and developing the concept of a national innovation system is connected with the scientists-economists of the neoclassical school of the 90s of the last century. However, apart from theoretical assessments, no complex research has been conducted in this direction.  The scientific novelty of the research: The article outlines the main directions of forming innovative economics based on the identification and analysis of the factors affecting innovative economics. The need for the involvement of state institutions in the process of forming an innovative economy is also substantiated in this article.